Response to Replication Report of "Negativity Drives Online News Consumption" - Claire E. Robertson; Nicolas Pröllochs; Philip Pärnamets; Jay J. Van Bavel; Stefan Feuerriegel (Institute for Replication (I4R), 2025)
We thank the authors for the extensive and thoughtful replication of our paper "Negativity drives online news consumption" (Robertson et al 2023). The authors conducted two types of direct replications and two types of conceptual replications of our analyses, and in all cases, found our main claim - that negative language drives news consumption - was highly robust. Indeed, they were able to exactly reproduce our key results and found they were robust to alternative model specifications and analytic decisions. We highly appreciate the depth of the replication, such as providing extensive documentation in their software repository as well as experimenting with additional methods based on large language models (LLMs). Overall, this gives us much greater confidence in the main conclusion from our original paper - that negative drives online news consumption in the Upworthy archive.
Keywords: 330